2021
DOI: 10.3390/jcm10214959
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cardiometabolic Disease with Psychological Factors in Colombian People during the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: During the COVID-19 pandemic, psychological disorders have been documented in the population, and their exacerbation in vulnerable populations such as those with Cardiometabolic Diseases (CD) might challenge health systems. This study determined psychological factors associated with CD in Colombian adults during the COVID-19 pandemic. For this purpose, 284 persons were evaluated, 142 without CD and 142 with CD. Sociodemographic data were collected, and the International Physical Activity Questionnaire (IPAQ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
1
0
3
Order By: Relevance
“…Educador físico enfocado en el área del fitness con amplia experiencia y conocimiento en la prescripción de ejercicio con diversos medios y métodos entrenamiento para de la promoción de la salud. Correo electrónico: ematurin@ estudiante.uniajc.edu.co L a pandemia por COVID-19 fue notificada por primera vez en China en el año 2019, esta enfermedad infecciosa causada por el virus Sars-CoV-2 generó un impacto mundial sobre el estilo de vida de las personas (García-Garro et al, 2021). En Colombia se confirmó el primer caso el día 6 de marzo del año 2020, por tal motivo se empezaron a implementar diversos controles como el aislamiento y la cuarentena para mitigar su propagación (Sedano-Chiroque et al, 2020).…”
Section: Ekkar Yesid Maturin Cajiaounclassified
See 2 more Smart Citations
“…Educador físico enfocado en el área del fitness con amplia experiencia y conocimiento en la prescripción de ejercicio con diversos medios y métodos entrenamiento para de la promoción de la salud. Correo electrónico: ematurin@ estudiante.uniajc.edu.co L a pandemia por COVID-19 fue notificada por primera vez en China en el año 2019, esta enfermedad infecciosa causada por el virus Sars-CoV-2 generó un impacto mundial sobre el estilo de vida de las personas (García-Garro et al, 2021). En Colombia se confirmó el primer caso el día 6 de marzo del año 2020, por tal motivo se empezaron a implementar diversos controles como el aislamiento y la cuarentena para mitigar su propagación (Sedano-Chiroque et al, 2020).…”
Section: Ekkar Yesid Maturin Cajiaounclassified
“…La pandemia ocasionada por el síndrome respiratorio agudo severo SARS CoV-2, es una enfermedad infecciosa y es catalogada como un virus altamente transmisible, este se propaga ya sea por nariz o boca a través de gotículas y por medio de enlaces cercanos, es decir, persona a persona (Long et al, 2022). Por otro parte, el mundo ha sufrido a causa de este virus, ya que ha repercutido negativamente de manera leve o moderada en la vida cotidiana de las personas, en vista de que afecta las labores diarias, la salud física, mental y el bienestar del ser humano (García-Garro et al, 2021;Maguiña Vargas et al, 2020)…”
Section: Covid-19unclassified
See 1 more Smart Citation
“…Other studies have shown that newly diagnosed diabetes is more prevalent in patients following COVID-19 infection, with one in every ten COVID-19 patients diagnosed with new onset diabetes mellitus [15,23]. In addition to metabolic health outcomes secondary to diabetes, some subgroups, specifically those with cardiometabolic disease [24], were at an increased risk of poor mental health outcomes, had depressive symptoms [25], and poor sleep quality [26]. Other negative behavioral activities included reduced physical activity [27,28] and increased alcohol consumption [26].…”
Section: Introductionmentioning
confidence: 99%